2021
DOI: 10.1038/s41598-021-88943-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing rumen microbiota and CAZyme profile of Indian dromedary camel (Camelus dromedarius) in response to different roughages

Abstract: In dromedary camels, which are pseudo-ruminants, rumen or C1 section of stomach is the main compartment involved in fiber degradation, as in true ruminants. However, as camels are adapted to the harsh and scarce grazing conditions of desert, their ruminal microbiota makes an interesting target of study. The present study was undertaken to generate the rumen microbial profile of Indian camel using 16S rRNA amplicon and shotgun metagenomics. The camels were fed three diets differing in the source of roughage. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…This has contributed to the growing knowledge about the rumen microbiome to e.g., improve feed conversion efficiency [ 1 ], and animals’ health [ 2 ], and mitigate methane emissions [ 3 ]. The ruminants microbiome’s ability to digest plants with high fibre content resulted in a large number of metagenomic studies, given the interest of the biobased industries in discovering microorganisms and lignocellulolytic enzymes to apply to their industrial processes [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This has contributed to the growing knowledge about the rumen microbiome to e.g., improve feed conversion efficiency [ 1 ], and animals’ health [ 2 ], and mitigate methane emissions [ 3 ]. The ruminants microbiome’s ability to digest plants with high fibre content resulted in a large number of metagenomic studies, given the interest of the biobased industries in discovering microorganisms and lignocellulolytic enzymes to apply to their industrial processes [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that Bacteroidota and Firmicutes are the dominant phyla existing within the rumen ecosystem (Amat et al, 2021 ; Hinsu et al, 2021 ; Virgínio Júnior et al, 2021 ). Consistently, the present study confirmed that Bacteroidota and Firmicutes are the top two predominant microbes regardless of media pH level or C. butyricum supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Another investigation aimed at generating a microbial profile for the forestomach of the Indian camel using 16S rRNA gene amplicon and shotgun metagenomics technology was carried out by Hinsu et al (2021) . In their study, they investigated the effect of diet, digesta fraction, and breed of camel on bacterial diversity and function.…”
Section: Fiber-degrading Bacteriamentioning
confidence: 99%
“…Other phyla among the most abundant were Proteobacteria, Fibrobacterota, Firmicutes-C, and Verrucomicrobiota. For carbohydrate hydrolyzing enzymes, the glycoside hydrolases were the most abundant among all ( Hinsu et al, 2021 ).…”
Section: Fiber-degrading Bacteriamentioning
confidence: 99%